Long-term Sub-zero Treatment of P/M Vanadis 6 Ledeburitic Tool Steel - a Preliminary Study - Jurci, Peter; Kusy, Martin; Ptacinova, Jana; Kuracina, Vladimir; Priknerova, Petra (Manufacturing Technology Journal, 2015)
The microstructure, the phase constitution and the tempering charts of Cr-V ledeburitic steel Vanadis 6 subjected to sub-zero treatment with various soaking times in liquid nitrogen have been investigated. The microstructures have been characterized using the light microscopy, scanning electron microscopy and X-ray diffraction. The hardness has been evaluated by Vickers method. The matrix is martensitic with certain amount of retained austenite, irrespectively to the time of sub-zero treatment. The amount of retained austenite, however, decreases up to the soaking time of 17 h and then remains almost constant. The microstructure of sub-zero treated steel contains enhanced portion of small globular carbides, as compared to conventionally heat treated material. These particles have a size of around 100 nm in most cases. The as-quenched hardness manifests a moderate increase due to the sub-zero treatment. The hardness decreases during subsequent tempering and this decrease is more pronounced in sub-zero treated samples.
Keywords: Cr-V ledeburitic steel; sub-zero treatment; retained austenite and martensite; carbides; hardness